Idea współpracy wirtualnych brokerów wiedzy dla małych i średnich przedsiębiorstw - Kotwica, Artur (The Idea of cooperation between SMES virtual knowledge broker, 2005)
Small and medium enterprises (SME) are very important component affects on stage of living. This is reason, why is so important to improve SME knowledge’s resources. The main target of this article is to present idea of virtual knowledge brokers for SME and to show cooperation between themselves
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 127-134